Aspectos clínico-epidemiológicos e análise espacial da hanseníase no município de Lago da Pedra MA - SILVA, Walquíria do Nascimento (2018)
Introduction: Hansen’s Disease, known since biblical times as leprosy, is an infectious disease caused by Mycobacterium leprae which has a chronic evolution manifested mainly by cutaneous lesions with diminished thermal, painful and tactile sensitivity. Maranhão was the Brazilian state with the highest number of new cases of leprosy in 2014 (3,632), whose fact classifies it as hyperendemic. Objective: To describe the clinical-epidemiological aspects and spatialization of leprosy in Lago da Pedra, Maranhão, Brazil from 2001 to 2016. Methodology: This is a quantitative and retrospective study with a descriptive approach, analysis of the environmental context and geographical distribution in health. All the patients enrolled in the Hansen’s Disease Control Program of this municipality, from 2001 to 2016, were included in the study. The georeferencing of the urban area and rural area was performed through Garmin eTrex® 10 GPS, totaling the collection of 17 geographical points where all the basic health units are located. Results:: The majority of the patients were male (57.9%) and the most frequent operational classification was multibacillary (58.1%), with a higher association among young adults aged 20-59 (65.1%) and the clinical form with the highest dhansiagnosis was the dimorphic form (72.9%) followed by the indeterminate form in children under 15 years old (58.0%). Over the years, the average detection coefficient was 159.8 cases per 100 million inhabitants in adults and an average of 14.3 cases per 100,000 inhabitants under the age of 15 years. Conclusions: This research discusses the importance of studying socioenvironmental variables and Hansen's Disease. The high indice of detection among the inhabitants of Lago da Pedra calls attention to the epidemic of the disease and draws our attention to the need of more studies in such region